Biological Activity of Natural Secondary Metabolite Products - Toshio Morikawa (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Natural secondary metabolite products, which are isolated from plants, animals, microorganisms, etc., are classified as polyketides, isoprenoids, aromatics (phenylpropanoids), alkaloids, etc. Their chemical diversity and variety of biological activities have attracted the attention of chemists, biochemists, biologists, etc. The Special Issue on "Biological Activity of Natural Secondary Metabolite Products" is intended to offer biological active natural products as candidates and/or leads for pharmaceuticals, dietary supplements, functional foods, cosmetics, food additives, etc. The research fields of this Special Issue include natural products chemistry, phytochemistry, pharmacognosy, food chemistry, bioorganic synthetic chemistry, chemical biology, molecular biology, molecular pharmacology, and other related research fields of bioactive natural secondary metabolite products. Original research and review articles on all topics in these research fields are invited. I am looking forward to receiving many submissions from outstanding experts in these research fields.